Evaluation of phenolic compounds, antioxidant activity and bioaccessibility in white crowberry (Corema album) - Andrade, Sónia C.; Guiné, Raquel; Gonçalves, Fernando J. A. (Journal of Food Measurement and Characterization, 2017)
This work aimed at evaluating bioactive compounds with antioxidant activity in Corema album berries. The phenolic properties were evaluated in different extracts from lyophilized samples of pulp and seeds, namely total phenolic compounds, ortho-diphenols, flavonoids, tannins and antioxidant activity by DPPH and ABTS methods. Furthermore, this study also aimed to assess the bioaccessibility of total phenolic compounds and their antioxidant activity through an in vitro simulation of the different stages of the gastrointestinal tract. The results showed high contents of total phenolic compounds (463 – 1614 mg GAE/100 g), of ortho-diphenols (11 – 23 mg GAE/100 g), of flavonoids (324 – 1437 mg QE/100 g) and of tannins (267 – 871 mg/100 g). The antioxidant activity varied in the ranges 25 – 42 and 52 – 80 micromol TE/g, respectively for DPPH and ABTS methods. Through the evaluation of bioaccessibility it was found that a high percentage of the total phenolics was lost so that only about 13 - 36% remained available for absorption, although there was a better preservation of the antioxidant activity, 18 – 49%, depending on the sample and extracting solution. info:eu-repo/semantics/publishedVersion